Sosialisasi Anti Bullying di MI Islamiyah Ngarum Kecamatan Sekaran Kabupaten Lamongan - Brilianti Ghefira Zakiyyah; Filliana Andalucya; Nabil Mikyal Adilla; Zulfanabil Munir; A.F. Suryaning Ati MZ (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2024)
Bullying is a disturbing social problem that affects society all over the world. Through a better understanding of this issue and continued collaborative action, we can work towards a safer, more empathetic and bullying-free society. Our KKN group took the initiative to hold an Anti-Bullying Socialization at MI Islamiyah Ngarum, Sekaran, Lamongan. This location was chosen because it is the most important subject for socialization regarding bullying, especially MI students, so that they have knowledge about the types and ways to prevent bullying. Activities will take place on August 25 2024 starting from the opening, socialization, games, ice breaking and gift giving. It was attended by all MI Islamiyah Ngarum students who were very enthusiastic about this activity.